Efektivitas Group Reminiscence Therapy Untuk Mengurangi Gejala Depresi Pada Komunitas Lansia: Systematic Review - Febrita Putri Gabinsla, Bernarda; Kurniawan, Afif (CV RIFAINSTITUT, 2022)
The growing number of elderly in Indonesia poses various challenges that must be faced. One of them is the increasing number of nursing homes to accommodate them. Although the elderly in the nursing home have gathered with their peers, in fact, many of them still suffer from depression. Therefore, group reminiscence therapy is needed in order to reduce the level of depression that experienced by the elderly. This study focuses on a literature review to provide a comprehensive understanding of the effectiveness of group reminiscence therapy in reducing symptoms of depression in the elderly community. Based on the results of the literature review, there are articles that reveal a significant effect on reducing symptoms, while others do not. Hence, a lot of research is still needed to examine this.